DEVELOPMENT OF PSYCHOLOGICAL TRAINING OF YOUNG TRACK AND FIELD GIRLS - Azizov Mukhammadjon Azamovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article highlights the improvement and effectiveness of the methodology of using action games in increasing the psychological training of young track and field athletes.